RANCANG BANGUN SMART CLOSED HOUSE PADA PETERNAKAN AYAM BROILER - Angga Dwipradipta, A A Gede; Dwija Ary Putra, I K J; Ardana, I P; Raka Agung, I G A P (Jurnal SPEKTRUM, 2024)
This research aims to enhance the growth performance of broiler chickens through the implementation of a smart closed house system. The prototype coop, with dimensions of 150 cmx 80 cm x 50 cm, has been successfully realized by integrating DHT22 and MQ135 sensors withexhaust fan and water pump actuators. The system is controlled by ESP32 DEVKIT, Long Range(LoRa) communication, and the Internet of Things (IoT). Collected data is sent to the Firebaseand can be accessed through an Android application. Testing demonstrates that the sensors andactuators operate according to changes in temperature, humidity, and ammonia gas conditionsinside the coop. LoRa communication testing involves sending sensor data (temperature,humidity, and ammonia gas) at distances of 1, 10, 100, 300, 500, and 600 meters. From thetesting of LoRa transceiver data transmission, a character loss percentage of 0% is observed at10 meters, while at 100 meters, there is a character loss percentage of 17.64%. Integration ofdata into Firebase is successful and displayed through the MIT App Inventor application onAndroid devices. Testing of chicken weight data indicates an increase in broiler chicken weight inthe smart closed house coop compared to secondary data from conventional closed house coops.The testing period spans from day 7 to day 21 of the chicken's age. The highest recorded weightis 1031 grams, with the average weight for all chicken samples at the age of 21 days being 940grams, 2.84% higher than the standard data from conventional closed house coops.